Penggunaan Sensor TCS3200 dan NodeMCU untuk Mendeteksi Warna Daun Padi dalam Menentukan Jumlah Pupuk Urea Bebasis IoT - Dani Sasmoko; Danang Danang; Padjar Setyo Budi; Muhammad Agus Kurniawan (Elkom : Jurnal Elektronika dan Komputer, 2020)
Technological developments encourage changes in the way decisions are made. In terms of stopping the application of urea fertilizer, farmers still rely on BWD observations. In this study, using the RnD method by directly observing the research location in the farmer group Gapoktan, in the village of Tosari, Kendan district and analyzing the problem then making a prototype which will be tested by experts. In this study, a tool was made using NodeMCU with TCS3200 sensor to detect color, which was then sent via the internet to the database using IoT technology. In this study, using several trials with different parameters of urea fertilizer use and the results of the TCS3200 sensor can detect colors according to what is on the BWD and send data to the database via the internet. In this system, farmers can recommend the use of suitable urea fertilizers outside a certain area so as to minimize errors in the observation on BWD, this will make the use of urea fertilizer to be the right dose.